Front Cover: Dendritic‐Like Molecules Built on a Pillar[5]arene Core as Hole Transporting Materials for Perovskite Solar Cells (Chem. Eur. J. 31/2021). Issue 31 (21st May 2021) - Bettucci, Ottavia; Pascual, Jorge; Turren‐Cruz, Silver‐Hamill; Cabrera‐Espinoza, Andrea; Matsuda, Wakana; Völker, Sebastian F.; Köbler, Hans; Nierengarten, Iwona; Reginato, Gianna; Collavini, Silvia; Seki, Shu; Nierengarten, Jean‐François; et al.
Abstract : Dendritic‐like hole transporting materials for perovskite solar cells have been prepared by functionalization of a clickable pillar[5]arene core with triarylamine dendrons. Importantly, the apparent structural complexity of the resulting compounds is not associated to a difficult synthesis which is a major advantage for applications in the field of organic electronic materials. More information can be found in the Full Paper by S. Collavini, S. Seki, J.‐F. Nierengarten, A. Abate, J. L. Delgado, et al. (DOI: 10.1002/chem.202101110 ).